Strategy Deployment and Spotify Rhythm - and Scotl, Karl (2016)
Last month, Henrik Kniberg posted slides from a talk he gave at Agile Sverige on something called Spotify Rhythm - "Spotify’s current approach to getting aligned as a company". While looking through the material, it struck me that what he was describing was a form of Strategy Deployment. This interpretation is based purely on those slides - I haven't had a chance yet to explore this more deeply with Henrik or anyone else from Spotify. I hope I will do some day, but given that caveat, here's how I currently understand the approach in terms of the X-Matrix Model.